Internet of Things applied to Aquifer Monitoring Systems: A survey (2020)
The interaction between the oceanic and continental basins has been of general interest among the scientific community of multiple disciplines, from the physical perspective of how the interaction of fresh and salt waters mutually modulate their hydrodynamic behavior, and how this in turn determines the transport of sediments, nutrients and other tracers, in addition to inducing changes in the morphodynamics of the river and / or coastal-oceanic zone. Due to the importance of technology for the prevention of different environmental phenomena, this article aims to show the systematic review of the literature about different applications that allow software and hardware interaction to support decision making in the sense of aquifers.